Some comments on the clinical neurological signs in a mongrel puppy during the suckling period - Case report - Barbosa, Larissa Licurci de Oliveira; Ramos, Maria Isabel Menezes; Leal, Paulo Daniel Sant’Anna; Lopes, Carlos Wilson Gomes (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Barbosa L.L. deO., Ramos M.I.M., Leal P.D.S. & Lopes C.W.G. Some comments on the clinical neurological signs in a mongrel puppy during the suckling period - Case report. [Alguns comentários sobre os sinais clínicos neurológicos num cão lactante sem raça definida – Relato de caso]. Revista Brasileira de Medicina Veterinária, 38(Supl 3):103-108, 2016. Programa de Pós-Graduação de Ciências Veterinárias, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro. BR 465 km 7. Campus Seropédica, RJ 23.890-000, Brasil. E-mail: pauloleal@ctiveterinario.com.br In the clinical routine of dogs, to perform an effective treatment of the morbid condition the diagnosis is fundamental and this objective is reached with observation of the evolution and in laboratory findings where the intercurrent infections have been observed frequently. We report a case of clinical laboratory diagnosis in Toxocara canis infection associated with the serological response to Neospora caninum in a lactating canine, with neurological and gastrointestinal clinical signs. In this way, the value of the clinical examination of feces in the serological diagnosis, demonstrating the need for greater attention to the diagnosis of multiple infections by different parasitic agents, allowing recovery of the patient after adequate treatment.